The impacts of shale natural gas energy development on outdoor recreation: A statewide assessment of pennsylvanians. (September 2019) - Ferguson, Michael D.; Lynch, Myles L.; Powers, Samantha L.; Barrett, Austin G.; Evensen, Darrick; Graefe, Alan R.; Mowen, Andrew J.
Abstract: This mixed-methods study examined the impacts of shale natural gas energy development (SGD) related activities upon outdoor recreation in Pennsylvania. Much of the ongoing and proposed SGD infrastructure in Pennsylvania is located either within or adjacent to public lands, waters, and protected areas, raising concerns about the potential environmental and social impacts upon recreation stakeholders. The extensive body of SGD research within the United States has suggested there are numerous positive and negative impacts upon the general public. Yet, the impact of SGD upon outdoor recreation users remains unclear. While SGD impacts are becoming progressively evident to both recreationists and natural resource managers, few studies have sought to specifically assess the extent to which SGD alters outdoor recreation behaviors, experiences, and activities. This statewide survey of Pennsylvanians ( n  = 2240) found that 23.4% of respondents had encountered SGD related activities while participating in outdoor recreation. Study findings also noted that 13.8% of respondents had changed their outdoor recreation behaviors or experiences as a result of encountering SGD related activities. Moreover, a sub-sample, representing 12.3% of respondents, identified specific SGD related impacts (e.g., aesthetic, environmental, infrastructure) upon their outdoor recreation behaviors, experience, and activities which sometimes resulted in substitution behaviors and/or a lack of perceived 'fit' between the energy development and the landscape and environment. From a policy and management standpoint, study findings highlight the specific and nuanced impacts of SGD upon certain sub-populations of outdoor recreationists as well as the importance of assessing and communicating recreation experience and use impacts to all recreationists when planning, developing, and managing SGD and related decisions in the United States. Management Implications: This study found that only a small population of Pennsylvania outdoor recreationists were impacted by SGD related activities. In the regions of Pennsylvania where SGD was most prominent (e.g., North Central and Southwest), outdoor recreation impacts were considerably higher. Moreover, a sub-sample of respondents found that SGD impacted their outdoor recreation behaviors, their in situ recreation experiences, and/or the environmental setting and landscape in which they recreated. Study findings suggest a two-tiered communication approach, accounting for perceptions of both behavioral and/or landscape environmental quality impacts, may be the most comprehensive strategy for addressing and communicating the impacts of SGD upon outdoor recreationists.